Ethical Computing: From Meta Ethics to Data Ethics - Lee, Wanbil (Ethics International Press Limited, 2024)
Ethical Computing is a means to an end as well as an end to itself; a problem, and a solution to a problem. It is the application of computer ethics in striving for doing-the-right-thing effectively in cyberspace or an information-intensive and technology-driven environment. The book addresses the realities of using computers while measuring up to the hexa-dimension metric (technically effective, financially viable, legally valid, ethically and socially acceptable and ecologically sustainable) manifested in applications from problem to ethical solution. This book collects work and research in practise and teaching across decades, covering a multitude of fields including information technology and engineering, computer audit & data governance, law practice and enforcement, and public and business administration. This is useful reference for researchers, teachers and students in all fields of information technology. It will also be useful for Chief Information Officers and Chief Technology Officers (CIOs and CTOs) and information systems auditors, and specialist IT law practitioners.